Halal food perspektif tafsir Kemenag: Studi analisis konten @tammyukhti mengkampanyekan real food - M Zakian Ifada; Lutfiah Putri Az-Zahra; Afita Adzaniah; Lukman Fajariyah (Nur Science Institute, 2025)
The shift in modern consumption patterns, marked by increased intake of instant and processed foods, has raised concerns about health and religious matters. Islam emphasizes the concept of halal and thayyib (good) food, which focuses not only on legal permissibility but also on health and overall benefits. This study aims to analyze the concept of halal food from the perspective of the Ministry of Religious Affairs (Kemenag) tafsir and to evaluate the effectiveness of the real food campaign promoted by the social media account @tammyukhti in raising public awareness of healthy, halal eating. A qualitative method was used, combining literature review and netnographic analysis to observe content and interactions on digital platforms. The findings reveal that Kemenag's interpretation stresses the importance of balancing halal status with nutritional quality. The real food campaign by @tammyukhti has been effective in raising awareness of the benefits of consuming natural, minimally processed foods, though challenges remain in shifting consumption habits. The study recommends enhancing halal food education through social media and fostering collaboration between government, academia, and health practitioners to strengthen public understanding of halal and thayyib.